Improved methods to capture the total societal benefits of zoonotic disease control: Demonstrating the cost-effectiveness of an integrated control programme for Taenia solium, soil transmitted helminths and classical swine fever in northern Lao PDR - Okello, Walter O.; Okello, Anna L.; Inthavong, Phouth; Tiemann, Tassilo T.; Phengsivalouk, Ammaly; Devleesschauwer, Brecht; Shaw, Alexandra; Allen, John (Public Library of Science, 2018)
Background